2006
DOI: 10.1103/physrevb.73.165311
|View full text |Cite
|
Sign up to set email alerts
|

Coulomb-interaction effects on the electronic structure of radially polarized excitons in nanorings

Abstract: The electronic structure of radially polarized excitons in structured nanorings is analyzed, with emphasis in the ground-state properties and their dependence under applied magnetic fields perpendicular to the ring plane. The electron-hole Coulomb attraction has been treated rigorously, through numerical diagonalization of the full exciton Hamiltonian in the non-interacting electronhole pairs basis. Depending on the relative weight of the kinetic energy and Coulomb contributions, the ground-state of polarized … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 34 publications
1
20
0
1
Order By: Relevance
“…This is indeed the case in the analyzed structure, where both the rings radii are larger than the effective Bohr radius, which is approximately equal to 12 nm in GaAs. A rigorous inclusion of the Coulomb interaction demonstrated that the optical excitonic AharonovBohm oscillations are also suppressed in the regime of week interaction [22], which exists in small rings. However, calculation of the exciton states is beyond scope of the present work.…”
Section: E(l) = E(-l)mentioning
confidence: 99%
“…This is indeed the case in the analyzed structure, where both the rings radii are larger than the effective Bohr radius, which is approximately equal to 12 nm in GaAs. A rigorous inclusion of the Coulomb interaction demonstrated that the optical excitonic AharonovBohm oscillations are also suppressed in the regime of week interaction [22], which exists in small rings. However, calculation of the exciton states is beyond scope of the present work.…”
Section: E(l) = E(-l)mentioning
confidence: 99%
“…This can be achieved by separating electron and hole using a static electric field, 14,15 or going to type II material combinations where electron and hole are confined in different regions. 12,13,16,17 In the original ABE idea, the particle path was assumed to lie in a region with zero magnetic field, which means to concentrate the magnetic flux into the middle of the ring. For a semiconductor nanoring of nanometer size, this is technically very demanding -if not impossible using state-of-the-art techniques.…”
Section: 13mentioning
confidence: 99%
“…Moreover, quantum rings have a unique magnetic field level dispersion: unlike quantum dots, the ground-state total angular momentum L in quantum rings changes from L =0 to L 0 by the application of a moderate external magnetic field B. [16][17][18][19][20][21] The values of B for which these transitions take place depend on the flux threading each ring, resulting in a different energy dispersion for excitons in QRMs with different ring radii. Thus, charge tunneling between states with distinct angular momentum is strongly suppressed by orbital selection rules.…”
Section: Introductionmentioning
confidence: 99%